Arterial lactate levels and their prognostic value in patients undergoing pulmonary thromboendarterectomy - Ramirez Ramos, Cristhian Felipe (2021)
Objective.  Evaluate the change of lactate levels and its prognostic role in the postoperative period of patients undergoing pulmonary thromboendarterectomy. Methods. Retrospective study between 2001 and 2019. Patients older than 18 years and who underwent pulmonary thromboendarterectomy were included. The U Mann Whitney test was performed to evaluate the change between lactate levels, and Cox regression analysis to evaluate the relationship with mortality. Areas under the curve were constructed for lactate levels. Results. Seventy-three patients were operated on during the study period. Median age was 51 years, 55% female. The median lactate on days 1 was 4.65 mml/L and on day 2 it was 1.62 mml/L with a change of 2.87 mml/L. No differences were found between the levels measured on day 1 and 2 between the people who died and those who did not on day 30. In the multivariate regression of COX, no relationship with mortality was found. The area under the curve shows regular performance on both day 1 and day 2 in predicting mortality outcomes. Conclusions. The behavior of the lactate in patients undergoing pulmonary thromboendarterectomy shows a rapid change during the first hours after the procedure. No role was found as a predictor of mortality neither in-hospital nor in follow-up.